Relationship between perceived physical literacy and obesity-related outcomes in adolescents: the EHDLA study - Domínguez-Martín, Gabriel; Tárraga-López, Pedro J.; López-Gil, José Francisco (Frontiers in Public Health, 2024)
The aim of the present study was to examine the relationship between perceived physical literacy and obesity-related outcomes among adolescents from Spain. This is a cross-sectional analysis including 845 Spanish adolescents (41.9% girls) aged 12 to 17 years from the Valle de Ricote (Region of Murcia) from the Eating Healthy and Daily Life Activities (EHDLA) project. Physical literacy was evaluated using the Spanish Perceived Physical Literacy Instrument for adolescents (S-PPLI). Body mass index was computed by taking the participants' body weight in kilograms and dividing it by the square of their height in meters, and body mass index (z score) and overweight/obesity and obesity were computed by the World Health Organization age-and sex-specific thresholds. Waist circumference was measured using a constant tension tape. Moreover, the waist-to-height ratio was calculated, and therefore, abdominal obesity was determined. Skinfold measurements were taken at the triceps and medial calf using calibrated steel calipers. Different significant areas were found in these associations. The first area indicated that the perceived physical literacy score was associated with body mass index (from 14 to 31 points), body mass index z score (from 9 to 33 points), waist circumference (from 9 to 33 points), waist-to-height ratio (from 13 to 32), skinfold (triceps) (from 9 to 33 points), skinfold (calf) (from 9 to 33 points), excess weight (from 9 to 34 points), obesity (from 9 to 33 points), and abdominal obesity (from 18 to 32 points). Conversely, a second area showed that high perceived physical literacy score was inversely related to body mass index (> 34 points), body mass index z score (> 34 points), waist circumference (≥ 33 points), waist-to-height ratio (> 34 points), skinfold (triceps) (≥ 33 points), skinfold (calf) (> 33 points), excess weight (≥ 35 points), obesity (≥ 34 points), and abdominal obesity (> 35 points). Physical literacy could play a crucial role in maintaining more desirable obesity-related outcomes in adolescents. Adolescents with high perceived physical literacy showed lower obesity-related indicators, as well as a lower probability of having excess weight, obesity, and abdominal obesity.